FUNCTIONAL AND ANATOMICAL OUTCOMES OF CHOROIDAL NEOVASCULARIZATION COMPLICATING BEST1-RELATED RETINOPATHY. Issue 7 (July 2017) - Khan, Kamron N.; Mahroo, Omar A.; Islam, Farrah; Webster, Andrew R.; Moore, Anthony T.; Michaelides, Michel
Abstract : Purpose: To describe the presenting features and functional outcomes in a series of patients with choroidal neovascular membrane complicating BEST1 -related retinopathy (Best disease and autosomal recessive bestrophinopathy). Methods: Retrospective review of consecutive cases at a tertiary care eye hospital. Patients were identified retrospectively over an 11-year period. Records were reviewed to extract demographic as well as functional and anatomical outcome data. Results: Fourteen eyes of 12 patients were identified (11 Best disease and 1 autosomal recessive bestrophinopathy). Median follow-up was 2.8 years (range 0.8–6). The median age at choroidal neovascular membrane discovery was 15.5 years (range 6–72). Choroidal neovascular membranes were active early in the disease course before vitelliruption. Seven eyes were treated with intravitreal bevacizumab, 7 eyes were monitored by observation alone. On average, patients required a single treatment (median = 1, range 1–10). The median gain in visual acuity was greater in the treated versus the observed group—0.46 versus 0.17 decimalized units of Snellen acuity, respectively ( P < 0.05 Mann–Whitney U test). Although a significant reduction in central macular thickness was evident in both groups, 150 μ m (treated) and 104 μ m (observed), active treatment was not associated with greater thinning than observation ( P > 0.05 Mann–Whitney U test). Conclusion: There is a high rate of spontaneous recovery of BEST1 -related choroidal neovascular membrane, and overall the authors observed a gain in visual acuity associated with a reduction in central macular thickness. Active treatment, here with intravitreal bevacizumab, is associated with better functional outcomes than observation alone. Abstract : Choroidal neovascularization is a rare cause of visual loss in patients with Best disease. Its optimal management is unknown. The authors highlight novel clinical features of disease and present outcome data suggesting that a better outcome might be obtained with anti–vascular endothelial growth factor therapy.